Forest in chains: a call for ethical approach when building with timber - Larsen, Claudia (My University, 2022)
Globalization facilitated many advancements in society. Through technology distances have been shortened, markets connected, and cultures shared. However, it has also magnified societal issues on a global scale. Illegal trades permeate all major industries, including the construction sector, and rely on the most vulnerable to build highly lucrative operations. “Global laws forbid the use of slave labour in the built environment, yet our buildings, and the materials that go into our buildings, are heavily reliant on slave labour.” (Grace Farms Foundation, 2020, p.4). In the forefront of sustainable materials, timber has been progressively taking ground for being both ecologically renewable and economically viable. However, it is also among the materials at the highest risk of embedded slavery and is often linked to illegal logging, jeopardizing the social aspect and holistic approach of the sustainable development goals. As architects, are we taking our share of responsibility and playing our part to ensure our specifications are not promoting such practices? Does the holistic sustainable perception of building with timber reflect the reality? Also, does the lack of ethical criteria within the construction process compromise the sustainability status of building with timber? This thesis aims to raise awareness of this pressing crisis, with an emphasis on the timber supply chain. Having the extraction of wood in the Amazon region of Brazil as a case study, seeking an understanding of the social impact of victims of forced labour, a major type of modern slavery within the sector. By understanding the main global actors, current practices, and policies, it pursues through design to gather the relevant information and arm professionals with the right questions in pursuit of breaking the cycle of vulnerability, exploitation, and re-victimization of those in forced labour. Continuous graphical reflections are used to support the findings and build the alternative perspectives on building with timber. A continuous construct to the final written and graphical manifestos: A call for ethical approach in design. Followed by a designer roadmap directing the reader to available tools to make this happen. A practical invitation for change.
Keywords: Forced labour within the built, environment, timber supply chain, illegal logging, social sustainability